2000
DOI: 10.1897/1551-5028(2000)019<0508:assdie>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Applying Species-Sensitivity Distributions in Ecological Risk Assessment: Assumptions of Distribution Type and Sufficientnumbers of Species

Abstract: Species-sensitivity distribution methods assemble single-species toxicity data to predict hazardous concentrations (HCps) affecting a certain percentage (p) of species in a community. The fit of the lognormal model and required number of individual species values were evaluated with 30 published data sets. The increasingly common assumption that a lognormal model best fits these data was not supported. Fifteen data sets failed a formal test of conformity to a lognormal distribution; other distributions often p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Often, the lower 95% CI for the HC 05 point estimate is selected as the concentration for protection. 70,71 If the data are lognormally distributed and an SSD approach is used, appropriate algorithms for these percentiles must be used.…”
Section: Guidelines Field Applications and Risk Assessmentsmentioning
confidence: 99%
“…Often, the lower 95% CI for the HC 05 point estimate is selected as the concentration for protection. 70,71 If the data are lognormally distributed and an SSD approach is used, appropriate algorithms for these percentiles must be used.…”
Section: Guidelines Field Applications and Risk Assessmentsmentioning
confidence: 99%
“…These correlations between species’ sensitivity and functional traits can cause ecosystem-level effects of chemicals to differ strongly between systems with similar species sensitivity distributions, affecting the representativeness of species-level effects for ecosystem-level effects. Methods that infer ecosystem-level effects from single-species bioassays, such as the SSD approach, have often been criticized for ignoring potential effects of species interactions. ,,,,, Here, it is shown that the correlation between species sensitivities and functional traits can partly account for this lack of information (Table and SI Table 5). In addition, inferring ecosystem-level effects requires measuring species-level effects that are relevant to both the aggregated ecosystem function and exposure scenario under assessment (Figures and ).…”
Section: Discussionmentioning
confidence: 99%
“…Most risk assessment procedures worldwide, however, still rely on single-species bioassays. Hence the reliability of the ecosystem-level effects that are inferred from the species-level effects measured in these bioassays, strongly depends on the assumptions made on how species-level and ecosystem-level effects are linked. Environmental risk assessment procedures generally need to balance pragmatism and environmental realism due to time or monetary constraints. , Therefore, simple theoretical models, such as the cumulative species sensitivity distribution (SSD), have increasingly been used for both regulatory and scientific purposes since the 1990s. SSDs are obtained by fitting a statistical distribution, generally a log-normal or log–logistic distribution, to the single-species toxicity data. , Environmental threshold concentrations are subsequently derived based on the adversely affected fraction of species that is considered acceptable, i.e. without putting the structure and functions of ecosystems at risk (e.g., 5% in EU legislation). ,, The SSD approach hence requires that the species from which it is derived are representative for all species in the system, and that a certain degree of functional redundancy between species exists so that ecosystem-level effects do not exceed species-level effects. ,, A variety of statistical and ecological effects can cause violations of these assumptions, which can consequently cause observed effects on ecosystem structure and function to deviate from those expected based on single species bioassays. ,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…† If multiple toxicity values were available for a single species, the geometric mean was used. 15 Sufficient toxicity data of MBT were not available, because of its low toxicity potential, and its risk to marine species was thus not quantied here.…”
Section: Ecological Risk Assessmentmentioning
confidence: 99%